Is there association between disease knowledge level, healthy lifestyle and quality of life of type 2 diabetic individuals? - Gezer, Ceren; Ulusan, Deniz Zehra (Refik Saydam National Public Health Agency (RSNPHA) turkhijyen@rshm.gov.tr, 2020)
Objective: In this study it is aimed to evaluate the level of disease knowledge, healthy lifestyle, quality of life and the relationship between of them in type 2 diabetic individuals. Methods: The study was conducted with 101 type 2 diabetic individuals who were referred to the Boron Center Family Health Center between June-October 2016. A questionnaire consisting of general characteristics, Healthy Lifestyle Behavior Scale II, Quality of Life Short Form 36, and Knowledge Level of Disease Questionnaire was applied to all individuals who applied to the center at the related dates by face to face. Body weight and height measured accoruding to tehniques and body mass index were calculated. Results: Out of 32.6% and 60.5% of the individuals were overweight and obese, respectively. The mean HbA1c level of individuals was 8.0±2.1. The mean total cholesterol, HDL and body mass index of females were found higher than males (p<0.05). Physical function, physical role strength, energy and pain averages of SF-36 components were higher in males than females (p<0.05). While more adoption of healthy lifestyle behaviors is related to the increase of quality of life, increase of disease knowledge level is related to healthy lifestyle behaviors such as health responsibility, nutrition, spiritual development and stress management and increase in quality of life (p <0.05). Conclusion: The quality of life of women with diabetes is lower than that of men. Healthy lifestyle behaviors in diabetic individuals are related to quality of life and can affect disease knowledge level, healthy lifestyle behaviors and quality of life. Selfmanagement including healthy lifestyle behaviors is therefore important in terms of ensuring metabolic control and increasing quality of life. Metabolic control parameters such as abdominal obesity, body composition and HbA1c as well as the body mass index need to be studied with a wider multicentral sample size that examines the disease knowledge level, healthy lifestyle behaviors and quality of life interactions in diabetic individuals. In addition, intervention studies may be useful in evaluating the effect of quality of life on individuals with type 2 diabetes by providing training to improve disease knowledge and self-management skills. © 2020 Refik Saydam National Public Health Agency (RSNPHA).
Tip 2 diyabetli bireylerde hastali[dotless]k bilgi düzeyi, sağli[dotless]kli[dotless] yaşam biçimi ve yaşam kalitesi ilişkili mi?
Keywords: Diabetes mellitus type 2; Healthy lifestyle; Quality of life